Measles virus infection of human keratinocytes: Possible link between measles and atopic dermatitis. Issue 2 (May 2017) - Gourru-Lesimple, Geraldine; Mathieu, Cyrille; Thevenet, Thomas; Guillaume-Vasselin, Vanessa; Jégou, Jean-François; Boer, Cindy G.; Tomczak, Katarzyna; Bloyet, Louis-Marie; Giraud, Celine; Grande, Sophie; Goujon, Catherine; Cornu, Catherine; et al.
Highlights: Measles virus infects human keratinocytes and modulates production of immunoregulatory cytokines. Anti-measles vaccination of patients with atopic dermatitis leads to the decrease production of thymic stromal lymphopoietin and CCL26 in patients skin. Transient improvement of SCORAD index is observed in vaccinated atopic dermatitis patients. Proof of concept for the vaccination therapy in atopic dermatitis. Abstract: Background: Measles virus (MV) infection is marked with a skin rash in the acute phase of the disease, which pathogenesis remains poorly understood. Moreover, the association between measles and progression of skin diseases, such as atopic dermatitis (AD), is still elusive. Objective: We have thus analysed the susceptibility of human keratinocytes to MV infection and explore the potential relationship between MV vaccination and the pathogenesis the AD. Methods: We performed immunovirological characterisation of MV infection in human keratinocytes and then tested the effect of live attenuated measles vaccine on the progression of AD in adult patients, in a prospective, double-blind study. Results: We showed that both human primary keratinocytes and the keratinocyte cell line HaCaT express MV receptors and could be infected by MV. The infection significantly modulated the expression of several keratinocyte-produced cytokines, known to be implicated in the pathogenesis of inflammatory allergic diseases, including AD. We then analysed the relationship between exposure to MV by vaccination and the progression of AD in 20 adults during six weeks. We found a significant decrease in CCL26 and thymic stromal lymphopoietin (TSLP) mRNA in biopsies from acute lesions of vaccinated patients, suggesting MV-induced modulation of skin cytokine expression. Clinical analysis revealed a transient improvement of SCORAD index in vaccinated compared to placebo-treated patients, two weeks after vaccination. Conclusions: Altogether, these results clearly demonstrate that keratinocytes are susceptible to MV infection, which could consequently modulate their cytokine production, resulting with a beneficial effect in the progression of AD. This study provides thus a proof of concept for the vaccination therapy in AD and may open new avenues for the development of novel strategies in the treatment of this allergic disease.